2020
DOI: 10.1093/eurheartj/suaa104
|View full text |Cite|
|
Sign up to set email alerts
|

Non-vitamin K oral anticoagulants for secondary stroke prevention in patients with atrial fibrillation

Abstract: The aims of this article are to review the evidence regarding the use of non-vitamin K oral anticoagulants (NOACs) for secondary stroke prevention as compared to vitamin K antagonists in patients with atrial fibrillation (AF) and in patients with embolic strokes of uncertain source (ESUS), and when to initiate or resume anticoagulation after an ischaemic stroke or intracranial haemorrhage. Four large trials compared NOACs with warfarin in patients with AF. In our meta-analyses, the rate of all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 44 publications
(68 reference statements)
0
23
1
Order By: Relevance
“…Similarly, in patients with an indication, the risks of all strokes were not significantly different between the NOAC and the VKA groups (Seeger et al, 2017;Kawashima et al, 2020;Didier et al, 2021;Van Mieghem et al, 2021). However, NOACs have been shown to be more effective than VKA for reducing the risk of stroke in patients with nonvalvular atrial fibrillation (Granger et al, 2011;Ajam et al, 2020;Diener et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, in patients with an indication, the risks of all strokes were not significantly different between the NOAC and the VKA groups (Seeger et al, 2017;Kawashima et al, 2020;Didier et al, 2021;Van Mieghem et al, 2021). However, NOACs have been shown to be more effective than VKA for reducing the risk of stroke in patients with nonvalvular atrial fibrillation (Granger et al, 2011;Ajam et al, 2020;Diener et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“… 34 Notably, in patients who may suffer from residual ischemic stroke, NOACs have been found to be more effective and safer for secondary stroke prevention compared with warfarin. 43 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, despite having a high thromboembolic risk in the stroke group, the observed annual rates of thromboembolism and major bleeding were still as low as 1.3 and 2.5%, respectively after LAAC. Diener et al reported that the annual rate of stroke/systemic embolism and major bleeding was 4.94% and 5.71% respectively in patients with AF and prior stroke /TIA post-NOAC treatment (23). Moreover, our study showed that the actual annual rates of thromboembolic events were significantly lower vs. predicted risks, yielding 77.5, 87.5, and 74.6% in RRR, with NNT 18,11, and 21 in the overall cohort, stroke group and non-stroke group, respectively.…”
Section: Discussionmentioning
confidence: 99%